Implicit Bias and the Illusion of Mediator Neutrality - Carol Izumi (Washington University Journal of Law & Policy, 2010)
Carol Izumi's Article, Implicit Bias and the Illusion of Mediator Neutrality, provides a reflective analysis of the complex challenges of a mediator’s ethical duty to mediate in a neutral manner against the behavioral realities of mediator thought processes, actions, motivations, and decisions. She explores the science of implicit social cognition and its application to mediation, and concludes that what actually constitutes neutrality is not clearly understood nor actualized. She then turns to one racial category, Asian Americans, to tease out ways in which implicit bias might affect mediators' "neutrality." According to Izumi, there is an unacceptable gap between the vision of mediator neutrality and the realities of biased mediator thoughts, behavior, and judgment. She challenges mediation teachers, trainers, and practitioners to "own up" to impartiality shortcomings and to undertake concrete measures to alter the ways they think and act. In the last section of the Article, she offers prescriptions to aid mediators in attaining "freedom from bias and prejudice."
Keywords: Mediator impartiality; Professional ethics; Prejudices; Stereotypes (Social psychology); Arbitrators; Justice discrimination; Legal ethics